Characterization of stem cells from the pulp of unerupted third molar tooth - Yasamin Hadaegh; Mahnaz Niknam; Armin Attar; Mohsen Khosravi Maharlooei; Maryam Sadat Tavangar; Ali Mohammad Aarabi; Ahmad Monabati (Wolters Kluwer Medknow Publications, 2014)
Context: Dental pulp stem cells (DPSCs) are the most diagnosed type of stem cells isolated from dental tissues. Previous studies demonstrate that tissues in earlier stages of development could be better stem cell resources for tissue engineering. Aims: In this study, aiming at finding younger stem cell resources, we chose the pulp of human unerupted third molar teeth when the crown was completely formed and the roots had not begun their development, Nolla's 6 th developmental stage (N6 th ). Materials and Methods: Surgical removal of the third molar was performed by aseptic technique with minimal trauma. The tissues were digested enzymatically and the resulted single cells were cultured. Immunophenotypic characterization of the cells was done via immunocytochemistry, immunofluorescence, and flow cytometry assays. Adipogenic and osteogenic differentiation potential of these cells was examined and confirmed by histochemical staining and reverse transcription-polymerase chain reaction analysis. Statistical Analysis Used: This study is descriptive. Results: N6 th -unerupted dental pulp cultured cells expressed DPSC markers: Vimentin, CD73, CD90, CD105, CD166, CD44, CD146, and STRO-1, but did not express hematopoietic cell markers: CD14, CD34, CD45, HLA-DR and were also negative for dentin sialoprotein negative showing an undifferentiated preodontogenic state. Adipocytes differentiated from N6 th -DPSCs were positively stained with Oil-Red-O and expressed both early and late adipocyte specific genes. Formation of Alizarin-red positive condensed calcium-phosphate nodules accompanied by strong expression of two osteogenic mRNAs, exhibited osteogenic differentiation. Conclusion: Based on the results of this study, we suggest that N6 th -DMSCs are a viable choice for cryo-banking and future usage in regenerative therapies; however, more investigations are necessary before clinical application can commence.